Optimized operation of local energy community with flexible energy resources providing local and system-wide flexibility services for DSO and TSO needs - Firoozi, Hooman; Khajeh, Hosna; Laaksonen, Hannu (IET, 2021)
This paper proposes the participation of a local energy community (LEC) in providing flexibility services to electrical network. In this regard, the LEC is proposed to provide active power support for the distribution system operator (DSO) in order to control voltage and manage the congestion of the local LV feeders. The LEC also simultaneously provides frequency containment reserves for normal operation (FCR-N) to the transmission system operator (TSO) for system-wide flexibility needs. The proposed model is implemented for a hypothetical case study. The results demonstrate the high potential of the LEC as a flexibility services provider for both DSOs and TSOs.
Keywords: flexibility needs; flexibility services; flexible energy resources; local energy community; optimal operation; fi=Sähkötekniikka|en=Electrical Engineering|